Serie van 8 foto's. Internatinale voetbalwedstrijd ter herdenking van de oprichting vam de A.N.C.B. 25 jaar geleden
Serie van 8 foto's. Internatinale voetbalwedstrijd ter herdenking van de oprichting vam de A.N.C.B. 25 jaar geleden.